2022
DOI: 10.3390/ijms23115986
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Inhibits Lipid Droplets Fusion and Growth via Reduction in Cidec and Its Regulatory Factors in Rat Adipose-Derived Stem Cells

Abstract: Metformin is still being investigated due to its potential use as a therapeutic agent for managing overweight or obesity. However, the underlying mechanisms are not fully understood. Inhibiting the adipogenesis of adipocyte precursors may be a new therapeutic opportunity for obesity treatments. It is still not fully elucidated whether adipogenesis is also involved in the weight loss mechanisms by metformin. We therefore used adipose-derived stem cells (ADSCs) from inguinal and epididymal fat pads to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Obesity can be prevented by regulating the various molecules involved in lipid accumulation in adipocytes. The first treatment for obesity is the inhibition of adipogenesis, which is the process by which preadipocytes differentiate into mature adipocytes ( 22 ). A number of anti-obesity agents that inhibit adipogenesis have been developed ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity can be prevented by regulating the various molecules involved in lipid accumulation in adipocytes. The first treatment for obesity is the inhibition of adipogenesis, which is the process by which preadipocytes differentiate into mature adipocytes ( 22 ). A number of anti-obesity agents that inhibit adipogenesis have been developed ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first treatment for obesity is the inhibition of adipogenesis, which is the process by which preadipocytes differentiate into mature adipocytes ( 22 ). A number of anti-obesity agents that inhibit adipogenesis have been developed ( 22 ). The present study confirmed that AHL effectively reduced the protein levels of CEBPα and PPARγ in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the expression of ABCG1 in condylar chondrocytes did not affect the expression of Cebpα and Fabp4, indicating that lipid biosynthesis and outflow to the outside of the condylar chondrocytes are two relatively independent processes, and abnormal biological forces may affect these two processes. Adiponectin and Perilipin1 are closely related to the content of mature lipid droplets formed in cells 44 . Therefore, when ABCG1 in condylar chondrocytes is inhibited or overexpressed, the amount of lipid accumulation in cells is directly affected, thereby affecting the expression of Adiponectin and Perilipin1.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity occurs when there is excessive accumulation of fat in adipose tissue ( 13 ). White adipose tissue (WAT) is known to increase because of excessive lipid accumulation within adipocytes, which is a major characteristic of obesity ( 14 ). Adipogenesis, the process by which preadipocytes differentiate into mature adipocytes, increases the number of mature adipocytes in WAT ( 15-17 ).…”
Section: Discussionmentioning
confidence: 99%